Conformation study of ɛ-cyclodextrin: Replica exchange molecular dynamics simulations. (5th May 2016) - Khuntawee, Wasinee; Rungrotmongkol, Thanyada; Wolschann, Peter; Pongsawasdi, Piamsook; Kungwan, Nawee; Okumura, Hisashi; Hannongbua, Supot
Highlights: Replica exchange MD can describe the conformational changes of CD10. The glycam06 is reliable for describing the flip of glucose subunit. The conformation behavior of CD10 in term of temperature change is reported. Abstract: There is growing interest in large-ring cyclodextrins (LR-CDs) which are known to be good host molecules for larger ligands. The isolation of a defined size LR-CD is an essential prerequisite for studying their structural properties. Unfortunately the purification procedure of these substances turned out to be very laborious. Finally the problem could be circumvented by a theoretical consideration: the highly advantageous replica exchange molecular dynamics (REMD) simulation (particularly suitable for studies of conformational changes) offers an ideal approach for studying the conformational change of ɛ-cyclodextrin (CD10), a smaller representative of LR-CDs. Three carbohydrate force fields and three solvent models were tested. The conformational behavior of CD10 was analyzed in terms of the flip (turn) of the glucose subunits within the macrocyclic ring. In addition a ranking of conformations with various numbers of turns was preformed. Our findings might be also helpful in the temperature controlled synthesis of LR-CDs as well as other experimental conditions, in particular for the host–guest reaction.